THE RESEARCH OF 10G-ETHERNET STANDARD IMPLEMENTATION IN UNIVERSITIES’ CLUSTERS USING STATISTICAL SOFTWARE - Shkarupilo, V. V.; Kasian, K. N.; Markin, A. G. (Radio Electronics, Computer Science, Control, 2011)
Анотація